Becoming Mapuche : person and ritual in indigenous Chile - Course, Magnus (Interpretations of culture in the new millennium., 2011)
Magnus Course blends convincing historical analysis with sophisticated contemporary theory in this superb ethnography of the Mapuche people of southern Chile. Based on many years of ethnographic fieldwork, Becoming Mapuche takes readers to the indigenous reserves where many Mapuche have been forced to live since the beginning of the twentieth century. In addition to accounts of the intimacies of everyday kinship and friendship, Course also offers the first complete ethnographic analyses of the major social events of contemporary rural Mapuche life - eluwun funerals, the ritual sport of palin, and the great ngillatun fertility ritual.